The impact of combining SRSD instruction with a brief growth mindset intervention on sixth graders’ writing motivation and performance - Camacho, A.; Alves, R. A.; Silva, M.; Ferreira, P.; Correia, N.; Daniel, J. (Contemporary Educational Psychology, 2023)
Self-Regulated Strategy Development (SRSD) is an evidence-based instructional approach combining background knowledge, writing, and self-regulation strategies to improve students’ writing motivation and performance. While the positive impact of SRSD on writing performance variables is well-established, mixed findings were found for motivational variables, namely self-efficacy. In addition, the impact of SRSD on motivational constructs other than self-efficacy—such as implicit theories—has received considerably less attention. In this study, we examined the impact of an SRSD instructional program about opinion text writing on two extensively studied writing performance variables (i.e., text quality and text length) and on two motivational variables (i.e., self-efficacy and implicit theories). Moreover, we tested whether adding a brief growth mindset intervention to SRSD instruction would result in gains in writing motivation and performance. To this end, we enrolled 191 sixth graders, from 11 classes, and their Portuguese language teachers to participate in a six-week intervention study. Using a quasi-experimental design, the classes were assigned to one of three conditions: (a) an active control condition (three classes); (b) an SRSD group (four classes); (c) an SRSD plus growth mindset intervention group (henceforth, SRSD+GM; four classes). Our results showed that both the SRSD and the SRSD+GM generally did not significantly differ from the active control group in self-efficacy and implicit theories of writing at posttest. The only exception was self-efficacy for ideation. Of note, the SRSD and the SRSD+GM groups outperformed the active control group in terms of text quality and text length. Our findings did not reveal an added value of a brief growth mindset intervention for SRSD instruction. Overall, our study showed that a six-week SRSD instructional program was effective in improving students’ self-efficacy for ideation and writing performance. However, the brief nature of both SRSD and mindset interventions may have precluded a broader positive impact on motivational beliefs, such as self-efficacy for conventions, self-efficacy for self-regulation, and implicit theories.